Intelligent question answering with natural language understanding and network-based advanced reasoning - Goh, Ong Sing; Fung, C.C.; Wong, W.; Sahib, S. (2005)
This paper presents NaLURI (Natural Language Understanding and Reasoning for Intelligence), a working question answering system whose technique is based on full-discourse natural language understanding and a novel approach of reasoning for semantic network that couples with two advanced reasoning features namely relaxation of constraint and explanation on failure.